A.P.M. Associação de Pais E Mestres: uma contribuição à sua compreensão - Antonio, Valmir Ederaldo de (2008)
The objective of this paper is to talk about how the participation of parents, teachers, students and community occurs in the A.P.M.’s in São Paulo and how this institution does the goals predicted in its standard statute. We also have as objective to talk about the A.P.M.’s since it origins until nowadays, to help the reader to understand the evolution and changes during the years. To achieve this purpose, we look for a dialogue with different authors inside a theoretical referential that looks for participation, charity work, collective person and autonomy. To realize this paper I used the empirical inductive method, in other words, we part from a single object to achieve the global one. As a methodological proceeding, I used the bibliographic research to find a referential theory and save important elements about the history of A.P.M.’s and I also used the documental analysis to read, understand and compare different laws, resolutions, decrees, communicates, statutes, etc; to do the final reflexion and do some considerations, I used my 23 years of experience as a teacher, principal and education supervisor, where I could participate in some A.P.M. groups several times in different schools. This paper has the following keywords: A.P.M, involvement, community, collective guy, autonomy and communitarian work